Permanência universitária: quando o pedagógico se une ao econômico - Mattos, Hellen Cristina Xavier da Silva (2020)
The subject of this research is part of the studies on the expansion and inclusion of Brazilian public higher education. We have as analysis object the university permanence from the students experiences who participate in a proposal of tutoring among peers for the permanence and academic success. The goal of this research is to analize the role of the Grupo de Tutoria do Programa de Acompanhamento Acadêmico do Estudante de Graduação (PAAEG) for the university permanence, problematizing the articulation between economic and pedagogic dimensions of the difficulties faced by the undergraduates, aiming to understand the developments of the institutional actions related to the pedagogical dimension of university permanence in adaptation strategies and in the formation of the student in the scientific field. The research is qualitative and uses Pierre Bourdieu’s contributions as its theoretical foundation. This is a field research, using online questionnaires and semi structured interviews, individual and in pairs, with twelve students who participate in the PAAEG tutoring group at UFSCar on the São Carlos campus and individual interviews only on three tutors that participate in the same program. The results indicated that the difficulties in adapting and staying at university related to the pedagogical dimension are related to the intensity of the studies, fragility of previous school contents, difficulties in the disciplines and pedagogical practices. University permanence is perceived by the students in questions related to the economic, pedagogical and psychological dimensions, and the institution has a special contribution in the economic dimension. Peer tutoring favors university permanence by offering academic support, welcoming to the student, familiarization with the university and a space where students feel more comfortable to expose their doubts and difficulties due to the closer relationship with tutors than with the professors. We infer that, in order to play the university field game, students needed to be equipped with school knowledge, cultural capital, and with a student habitus related to the field’s requirements, including in the face of hierarchical relationships with professors. We believe that the difficulties and situations of suffering experienced by students may be related to the university field’s pressure, especially for students who are still forming theirs university student habitus and acquiring the symbolic and cultural capital during the academic training. We understand that this suffering is intensified by the symbolic violence present in the gift ideology, which is reinforced by teaching practices that naturalize the academic work. The university´s permanence policy has been expanded with new proposals to support and welcome students, actions that are complementary to the financial support of scholarships, which are essential to the permanence. However, the pedagogic approach of peer tutoring has been the main strategy used by the institution to justify the increase in the Graduation Success Rate. In this way, contributing to academic success, PAAEG tutoring group also contributes to permanence. The student feels more capable, legitimized and strengthened to overcome the difficulties of the university field and graduate from the undergraduate course.